A sociophonetic investigation of ethnolinguistic differences in voice quality among young, South African English speakers - Wileman, Bruce Rory (School of African and GenderStuds, Anth and Ling, 2018)
Prior research has suggested that there may be differences in voice quality between black and white speakers of South African English who had attended well-resourced middle-class schools. The principal objective of the study is to address the question of whether there is any acoustic evidence of such differences. The study then proceeds to describe such acoustic evidence for differences in voice quality. The author interviewed 36 female South African English speakers (18 white and 18 black) between the ages of 18 and 22. The research subjects had all attended well-resourced middleclass schools. In order to control for the possibility of substrate influences on voice quality, all black participants were of an isiXhosa language background. High quality sound recordings were conducted, consisting of both a set of read sentences as well as semi-structured interviews, the latter of which formed the core dataset for the subsequent acoustic analysis. The acoustic data were analyzed using VoiceSauce, a program specifically designed for the acoustic analysis of voice quality. Measurements were based on automatically segmented speech samples using FAVE and PRAAT. The VoiceSauce measurement data were statistically analyzed by means of a linear mixed effects regression analysis and Wilcoxon rank sum tests using the statistical package R to evaluate the significance of ethnicity as a variable. The effect of ethnicity was found to be significant for several measures of spectral tilt (including for example, 2K*-5K, H4*-2K*, H1*-H2* and H1*-A1*) and cepstral peak prominence with a nearly significant effect for the subharmonics-to-harmonics ratio. Black speakers exhibited consistently higher values for most harmonic differential measures (for example, H1*-A1*) overall, while white speakers exhibited higher values for fundamental frequency, harmonics-tonoise ratio and cepstral peak prominence. The author concludes that the acoustic evidence is most consistent with the hypothesis that the white speakers overall typically use a voice quality iii characterized by greater vocal fold constriction, thickness and stiffness in comparison to the black speakers, hypothesized to use a voice quality characterized by more breathiness. By providing a description of voice quality variation, the research contributes towards a more complete account of sociolinguistic variation in South African English.